Upaya Peningkatan Mutu Kesehatan di Desa Romadhon Kecamatan Sungaiselan Tahun 2024 - Setyawati, Dewi; Kurrohman, Taufik; Siswanto , Siswanto; Mihalda, Ze Refaldi; Rohmat , Rohmat; Rahmadhani, Tika; Safitri, Rahma; Nabiqa, Shalma; Fadilah, Maudy Arysta (Penerbit Goodwood, 2025)
Purpose: This activity aims to empower the community in addressing three major issues in Romadhon Village, Sungaiselan District, namely stunting among toddlers, improper parenting patterns, and juvenile delinquency. The program focuses on increasing community awareness and participation through educational and participatory approaches. Methodology/approach: The activities were carried out through lectures, counseling sessions, field observations, focus group discussions (FGDs), and direct assistance. Data were collected using questionnaires and observations related to family conditions, parenting patterns, and adolescent behavior. Results/findings: The results showed an improvement in community understanding of the importance of proper parenting in preventing stunting. The counseling program and provision of supplementary feeding (PMT) to ten stunted children increased family nutritional awareness. Parenting education for mothers and socialization on juvenile delinquency through lectures on the dangers of drugs and the installation of anti-smoking banners encouraged active youth participation in the village. Conclusions: This community empowerment program effectively enhanced family health awareness, improved parenting practices, and reduced juvenile delinquency behavior. The synergy between students, village authorities, and the community was a key factor in the program’s success. Limitations: The short implementation period limited the measurement of long-term impacts on behavioral change within the community. Contribution: This activity can serve as a model of education- and participation-based community empowerment to improve public health in rural areas.